The level of Psychological Stresses Of mothers Of Children With Intellectual Disability according to some variables “ A field study in Lattakia city” - Charrouf, Ansab; kikhia, Nagham (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The objective of this study is to know the level of psychological stresses of mothers of children with intellectual disability in Lattakia city. it aimed to find differences in the psychological stresses according to some variables : mothers educational level, child's gender , and the child's disability degree. The sample consisted of 34 mothers . The test of Sertawi& Abdul Aziz (1998) had been used. The results indicated that 14.7% of the participants experienced high level of psychological stress, 58.8% experienced medium level and 26.5% didn’t show any symptoms of psychological stresses. The study did not show any notable differences regarding variables: mothers educational levels, child's gender or the child's disability